Un debate sobre la identidad femenina en el renacimiento - Cagnolati, Antonella (CUADERNOS KÓRE, 2011)
The debate about the female ontology was very vivid in 16th century in England, owing to the lack of an heir for the succession to Henry VIII Tudor. The first treatise, discussing in a logical way, the female capacity to exercise the political power was The Defence of Good Women by Thomas Elyot, a dialogue in the ancient Rome, aiming at comparing the theories of Aristotle and Plato about inferiority/equality of women. The main character is Zenobia, relevant example of virtue and clever government. The debate ends with the affirmation that a woman is "more perfect than a man".
Keywords: Renaissance; Zenobia; philosophical dialogue; virtue; querelle des femmes; learning